Clinicopathologic Significance of Survivin Expression in Relation to CD133 Expression in Surgically Resected Stage II or III Colorectal Cancer - Wanlu Li; Mi-Ra Lee; EunHee Choi; Mee-Yon Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Background Cancer stem cells have been investigated as new targets for colorectal cancer (CRC) treatment. We recently reported that CD133+ colon cancer cells showed chemoresistance to 5-fluorouracil through increased survivin expression and proposed the survivin inhibitor YM155 as an effective therapy for colon cancer in an in vitro study. Here, we investigate the relationship between survivin and CD133 expression in surgically resected CRC to identify whether the results obtained in our in vitro study are applicable to clinical samples. Methods We performed immunohistochemical staining for survivin and CD133 in surgically resected tissue from 187 stage II or III CRC patients. We also comparatively analyzed apoptosis according to survivin and CD133 expression using terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling. Results The results of the Mantel-Haenszel test established a linear association between nuclear survivin and CD133 expression (p = .018), although neither had prognostic significance, according to immunohistochemical expression level. No correlation was found between survivin expression and the following pathological parameters: invasion depth, lymph node metastasis, or histologic differentiation (p > .05). The mean apoptotic index in survivin+ and CD133+ tumors was higher than that in negative tumors: 5.116 ± 4.894 in survivin+ versus 4.103 ± 3.691 in survivin- (p = .044); 5.165 ± 4.961 in CD133+ versus 4.231 ± 3.812 in CD133- (p = .034). Conclusions As observed in our in vitro study, survivin expression is significantly related to CD133 expression. Survivin may be considered as a new therapeutic target for chemoresistant CRC.